The synthesis, reactivity and application of functionalized alkyl transition metal complexes - Liao, Yi-Hsien (Department of Chemistry, 2017)
Haloalkyl transition metal complexes can be precursors for a wide range of useful complexes. In Chapter 1, the bromohexyl iron complex, [CpFe(C0)2{(CH2) 0Br}] has been prepared and new information on electrochemical and thermal behaviour of (CpFe(C0)2{(CH2) 6Br}] has been obtained from cyclic voltammetry and differential scanning calorimetry respectively. The chemical reactivity of (CpFe(C0)2{(CH2) 0Br}] with various reagents including NaOMe, a cobaloxime anion, Meli, NaN3 , magnesium metal, phenol derivatives ( phenol, resorcinol, 4-hydroxybenzyl alcohol and 3,5- dihydroxybenzyl alcohol), trityl salt, PPh3, and CO/AgBF4 has also been studied. The new complexes that we obtained are namely: [CpFe(CO)(L){C=O(CH2) 0Br}] ( L = CO and PPh3 ) from the reactions with CO/AgBF4 and PPh3 respectively, . [CpFe(C0)2{CH2=CH{CH2) 4Br]PF6 from the reaction with the trityl salt, and oofunctionalized hexyl iron complexes. All these new complexes have been characterized by standard analytical and spectroscopic methods. The results showed that chemoselective reactions of [CpFe(C0)2{CHJ6Br] can occur at either the metal centre or the co-functional group. The results are also compared to those obtained for alkyl and functionalized alkyl iron complexes.